PERSEPSI MAHASISWA JURUSAN KOMUNIKASI DAN PENYIARAN ISLAM TERHADAP PENYEBARAN BERITA HOAKS DI MEDIA SOSIAL - Musdalifah Musdalifah; Nurdin Nurdin; Fitriningsih Fitriningsih (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
This paper discusses students’ perception on hoax postings on son social media sites. The focus of the study is to find out how students' of IAIN Palu perceive hoax dissemination on social media. This research is a qualitative study. In collecting data researchers used in-depth interview methods, observations, and documents. The subjects of this study are students majoring in Islamic Communication and Broadcasting starting from second semester two to the eight semester. The results of this study indicate that students have different perceptions on hoax dissemination, where some students realize that it is important to read, and examine carefully information or news received from social media sites, so that they can find out about the authenticity of the news or information, and it is not wise to share news that is not yet known to be true, and there are also some students who are actually involved in spreading hoaks due to trial and error.